HHHHHHHHHEEEEEEEEELLLLLLLLLLPPPPPPPPPPP????????????

## 4(3-2x)=-44

# 3 Answers

** 4(3 - 2x) = -44**

I'm assuming you are looking to solve for the only unknown variable, that being 'x'. To do so, you need to isolate this variable to one side of the equation.

First, divide both sides of the equation by 4:

(4(3 - 2x))**/4** = (-44)**/4**

(**4/4**)(3 - 2x) = -(44/4)

(3 - 2x) = -(11)

**3 - 2x = -11**

Next, subtract 3 from both sides of the equation and combine like terms:

3 - 2x **- 3** = -11 **- 3**

** 3 - 3** - 2x = -11 - 3

** -2x = -14**

Then, to solve for x, divide both sides of the equation by -2:

(-2x)**/-2** = (-14)**/-2**

(**-2/-2**)x = (**-/-**)(14/2)

**x = 7**

You can check to see if this is the correct answer by plugging in **x = 7** into the original equation:

4(3 - 2**x**) = 4(3 - 2(**7**)) = 4(3 - 14) = 4(-11) = -44

First, let's distribute the left hand side:

4*3 - 4*2x = -44

12 - 8x = -44

Next, isolate our variable. We're going to do this by subtracting 12 from both sides of the equation.

-8x = -44 - 12 = -56.

Lastly, divide by -8 on both sides to get x completely alone.

x = -56/-8 = 7.

You can check your answer by plugging 7 in for x and seeing what comes out!

4(3-2*7) = 4(3-14) = 4(-11) = -44.

4(3 - 2x) = -44

use distributive law of multiplication by multiplying 4 and 3 and 4 and -2x:

12 -8x = -44

-44 -12 = -8x

-56 = -8x

**x = 7**